Freshwater Management Discourses in the Northern Peruvian Andes: The Watershed-Scale Complexity for Integrating Mining, Rural, and Urban Stakeholders - Mercado-Garcia, D. (2023)
The Peruvian environmental action plan seeks headwaters protection as one of its integrated watershed management objectives. However, heterogeneous social and environmental conditions shape this freshwater management challenge at subnational scales. We have noticed different interpretations of this challenge. To map the debate, understand the diverse interpretations, and frame political choices, we conducted semi-structured interviews with institutional and non-institutional stakeholders for performing discourse analysis in an Andean watershed where mountaintop gold mining, midstream farmers, and the downstream Cajamarca city coexist. One discourse dominates the debate on protecting the freshwater supply and argues the importance of river impoundment, municipal storage capacity, and institutional leadership. The other two discourses revolve around protecting the mountain aquifer. The second discourse does so with a fatalistic view of headwaters protection and rural support. The third discourse partially shifts the debate towards the need for improving rural capacity building and (ground)water inventories. To understand evolutions in society, it is crucial to understand these three discourses, including the types of knowledge that actors present as legitimate, the attributed roles to all stakeholders, and the kinds of worldviews informing each discourse. The interaction among discourses could hinder integrated watershed management at worst or, at best, help inspire multi-stakeholder collaboration.